RANCANG BANGUN MESIN SANGRAI BIJI KOPI OTOMATIS KAPASITAS 1 KILOGRAM - Aryal Fernando, Vrizky; Pratama, Febri; Febriansyah, Aan; Palupi, Dora (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
Coffee is an important commodity that has high economic value, both at the national and global levels. The roasting process of coffee beans plays a crucial role in determining the flavor and quality of the final product. However, the automatic roasting machines available on the market are generally intended for large-scale production with prices that are not affordable for Micro, Small, and Medium Enterprises (MSMEs). Therefore, this research aims to design and build an economical and easy-to-operate automatic coffee bean roasting machine with a capacity of 1 kilogram. This machine uses a manual heating system, manual temperature control, and is equipped with temperature sensors and an LCD display to monitor the roasting process. The design and construction of this machine are expected to provide an effective and efficient solution for MSMEs to improve the quality of their roasted coffee production. Additionally, an economic study was also conducted to compare the production costs of this machine with the market prices of similar machines.